Between buzzwords and bodies: investigating the ambiguities of Allyship with Judith Butler’s relational thinking - Vosloo, Jana Lydia (Stellenbosch : Stellenbosch University, 2020)
Thesis (MA)--Stellenbosch University, 2020.